Contextualizing the experiences of Black pregnant women during the COVID-19 pandemic: 'It's been a lonely ride' - Alicia A. Dahl; Farida N. Yada; Shanika Jerger Butts; Annalise Tolley; Sophie Hirsch; Priyanka Lalgondar; Kala S. Wilson; Lindsay Shade (BMC, 2023)
Abstract The emergence of the COVID-19 pandemic significantly changed the prenatal care experience, specifically regarding medical appointments and social opportunities. It is critical to capture this change through the narratives of pregnant people, particularly those of marginalized populations, whose voices may often be underrepresented in the literature. This mixed-methods paper summarizes the experiences of 40 pregnant Black/African American (AA) women during the COVID-19 pandemic. A cross-sectional, online survey was administered between 2020 and 2021 to assess prenatal health and the impacts of the COVID-19 pandemic on patients' pregnancy experience. Coping behaviors during the pandemic were self-reported using the COPE-IS. Univariate analyses were conducted. An additional analysis of participants (n = 4) was explored through a week-long qualitative exercise using a photo documentation procedure. Photo-Elicitation Interviews (PEI) were conducted to capture and center their pandemic pregnancy experiences. Sources of stress during the pandemic varied, with the most common being financial concerns (n = 19, 47.5%). Over half of the sample (n = 18, 54.5%) self-reported increases in their positive coping behaviors during the pandemic, such as communicating with friends and family, talking to healthcare providers, listening to music, and engaging in spiritual practices-such as prayer. The four PEI study participants reflected on the impacts of social distancing on their prenatal experience and mentioned hospital and provider-related weariness due to their race. The findings of this study suggest that during the COVID-19 pandemic, Black/AA pregnant women in Charlotte, NC used social support, mindfulness practices, self-advocacy, and health literacy to navigate challenges present during their prenatal health experience. This paper highlights the personal, social, and structural experiences of pregnant women during a public health crisis so that responsive and effective programs or policies can be planned in the future.